Distribution of completion and elimination of horses participating in different distance of endurance race, and causes of elimination - Mohd Noor, Mohd Akmal (2015)
Four hundred and eighthy eight endurance race data were collected from 61 horses during Sultan Mizan Cup 2014 in different distance; 40 km (171 horses); 80 km (215 horses); 120 km (87 horses); and 160 km (15 horses). Out of 488 horses, only 340 horses (69.7%) were able to complete the endurance race and 148 horses (30.3%) were eliminated. In 40 km race, elimination due to the lameness and elevated heart rate was 46.9% respectively, meanwhile 6.2% were eliminated due to abnormal intestinal motility. For 80 km race , the cause of elimination due to lameness is 63.9%, elevated heart rate; 31.9% and abnormal intestinal motility; 4.2%. In 120 km race, elimination due to lameness is 55.6%, elevated heart rate; 38.9% and abnormal intestinal motility; 5.5%. Meanwhile, for 160 km race; 100% elimination is due to lameness. In 40 km race, elimination due to metabolic disorder is 53.1% and musculoskeletal; 46.9%. Meanwhile, in 80 and 120 km race, musculoskeletal elimination is 63.9% and 55.6% respectively, followed with metabolic disorder; 36.1% and 44.4% correspondingly. In 160 km race, all elimination is due to musculoskeletal abnormality.